PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS DISCOVERY LEARNING PADA MATERI ATURAN SINUS DAN COSINUS UNTUK PESERTA DIDIK KELAS X SMA/MA - Resvi Mardhatillah (Departemen Matematika, 2021)
The purpose of this research is to develop student worksheets on the rule of sine and cosine that is valid, practical and effective using the discovery learning model. This is because the student worksheets used in the learning process are still not able to facilitates students to be actively involved in discovering a concept or principle to construct their knowledge. The type of this research is Research and Development (R&D). The research data from the questionnaire were analyzed by using descriptive statistics, and the data from observation and interviews were analyzed by describtive techniques. This research used the Plomp model which consists of three phases, namely preliminary research, development or prototyping phase, and assessment phase. The results of this research are (1) the student worksheets developed has a very valid category with a validity value of 89,29%, (2) the student worksheets developed has a very practical category with a practicality value of 88,54%, (3) the student worksheet developed is effective for use with gain score value of 0,695 which is in the medium category. Based on the research results, it can be concluded that the developed student worksheets can be applied ini mathematics learning in schools. Keywords – Student Worksheet, Discovery Learning, The Rule of Sine and Cosine, Plomp